Firm Size and Growth in Ecuador's Trade Sector: An Analysis from an Industrial Economics Perspective - Núñez-Naranjo, Aracelly Fernanda; Haro, Diego Marcelo Lara; Mesías, Juan Pablo Martínez; Sarzosa, María José Sanchez (Journal of Ecohumanism, 2024)
This study examines the dynamics of firm growth in the trade sector from 2016 to 2021, utilizing Gibrat's Proportional Effect Law. Panel data and Arellano and Bond's dynamic GMM estimator were employed to analyze variables such as sales revenue, growth, age, innovation, and indebtedness. The results suggest that small firms grow more rapidly than large ones, contradicting the assumption of growth independence from initial size. Additionally, it was observed that the growth of commercial companies is not continuous and is negatively influenced by the previous period, challenging the assumption of independence between periods. Furthermore, evidence of diversity in corporate growth was found, which refutes the idea of a trend towards concentration and monopoly. Finally, age, innovation, and indebtedness were determined to exert a significant influence on firm growth.